Analisis potensi penerapan teknologi produksi bersih pada c-maxi alloycast, Yogyakarta - Dewi Masri; Wagiman Wagiman; Bertha Maya Sopha (Universitas Gadjah Mada, 2022)
CV C-Maxi Alloycast is an industry engaged in the manufacture of household appliances (pans) made of aluminum which is located in Yogyakarta. The aim of the study was to identify the potential application of clean production principles in CV C-Maxi Alloycast. The methods used were production process mapping, waste analysis through liquid waste testing and potential analysis of clean production principles. The results obtained for the production process were smelting aluminum and scrap, pouring molten metal into molds, lifting molds and providing coolant, lifting castings, turning, filing, quality control, storage and distribution. Based on the laboratory test, the characteristics of the liquid waste produced by the CV C-Maxi Alloycast were pH 8.9; COD 52.1 mg/L; BOD 21.4 mg/L; TSS 6660 mg/L; Fe 4,2440 mg/L; Cu 0.0130 mg/L; and Zn 0.0893 mg/L. All parameters indicate that the value meets the quality standard, but the TSS content did not meet the NAB (Threshold Value) which refers to the Regulation of the Minister of the Environment of the Republic of Indonesia No. 5 of 2014 and the Regulation of the Special Region of Yogyakarta (DIY) No. 7 of 2016. Clean production opportunities were: good housekeeping, application of 3R (Reduce, Reuse, Recycle) on solid waste, construction of B3 Waste TPS and capacity building of human resources. Environmental performance had increased based on the Green Industry Standard (SIH) from level 1 to level 2 with a value of 53% to 65% with the implementation of clean production. The economic performance of implementing clean production gains a profit of Rp. 77,412,000,-/year, then the second alternative, namely recycling aluminum scrap is an economical alternative to clean technology with a 5-year NPV value of Rp. 37,853,056,558,- Implementing clean production can have a positive impact on the environment and the economy.